1976
DOI: 10.1021/bi00654a007
|View full text |Cite
|
Sign up to set email alerts
|

The activation of factor V by factor Xa or α-chymotrypsin and comparison with thrombin and RVV-V action. An improved factor V isolation procedure

Abstract: Bovine plasma factor V has been isolated by a preparative procedure involving barium sulfate adsorption, QAEC extraction, poly(ethylene glycol) precipitation, and finally chromatography on a desulfated Sepharose 6B column. Factor V was recovered as a single peak in yields of 35-40% with a specific activity of 50-70 representing a purification of 1000-2000-fold relative to the starting plasma. The apparent molecular weight of the purified factor V was 439,000 +/- 5000. On sodium dodecyl sulfate gel and analytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

1979
1979
2006
2006

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…We observed that for the expression of amidolytic activity, RVV‐V and LVV‐V do not require a functional calcium binding site, since both FV activators retained amidase activity after treatment with the metal chelator EDTA (Table I). Furthermore, it has been demonstrated that both snake venom proteases activate FV in a calcium‐independent manner 17, 67…”
Section: Resultsmentioning
confidence: 99%
“…We observed that for the expression of amidolytic activity, RVV‐V and LVV‐V do not require a functional calcium binding site, since both FV activators retained amidase activity after treatment with the metal chelator EDTA (Table I). Furthermore, it has been demonstrated that both snake venom proteases activate FV in a calcium‐independent manner 17, 67…”
Section: Resultsmentioning
confidence: 99%
“…Bovine Factor V is more stable than its human counterpart, for which reason most of our knowledge derives from studies using bovine material (9)(10)(11)(12)(13)(14). However, only recently was bovine Factor V purified to Received for publication 26 February 1980 and in revised form 2 May 1980. homogeneity, by Nesheim et al (12) and by Esmon (13).…”
Section: Introductionmentioning
confidence: 99%
“…Tissue factor pathway inhibitor (TFPI) binds to TF-FVIIa-FXa to limit the production of FXa and FIXa by TF-FVIIa (3,4). Nevertheless, once produced, thrombin and the initially formed FXa activate small quantities of factor V (FV) to FVa and factor VIII (FVIII) to FVIIIa (5)(6)(7)(8). The activation of these two cofactors leads to the formation of two other essential procoagulant complexes, both involving FX, at the surface of procoagulant phospholipids in the presence of calcium ions (9), FIXa-FVIIIa and FXa-FVa complexes, which convert FX to FXa and prothrombin to thrombin, respectively.…”
mentioning
confidence: 99%